Providing a sustainable sonographer workforce in Australia: Clinical training solutions. Issue 4 (2nd November 2020) - McGregor, Rod; Pollard, Karen; Davidson, Rob; Moss, Cameron
Abstract: Introduction: At present, sonography in Australia is experiencing a workforce shortage and increasing demand for services. This shortage has been linked to a lack of clinical placements for sonography students, creating a need to develop solutions to the paucity of training opportunities. Methods: A three‐round ranking‐type Delphi analysis in conjunction with thematic analysis was used to develop and rank a list of potential solutions to the shortage of clinical placements. Participants were recruited purposively based on their roles in the field of sonography that involved management of students in clinical placements. Results: In total, 32 potential solutions were developed based on thematic analysis of open‐ended questionnaires completed by participants. Of which, 13 were deemed essential and ranked from most to least important. Discussion: The potential solutions developed in the present study has implications for how sonography services, governing bodies and universities could overcome barriers to providing clinical placements. The highest ranked solution among participants was support from management to employ student sonographers, with the remaining solutions primarily pertaining to assistance in structuring and financing placements, and further support from higher education institutions. It was recommended that future research focus on structuring and financing placements.